A Conceptual Model to Evaluate Secure Intention Behavior in Online Game Addiction Among Adolescents - Yaacob, Wan Mohd Yusoff Wan; Zakaria, Nur Haryani; Mat Aji, Zahurin (Multidisciplinary Applied Research and Innovation, 2023)
Recently, there is enormous views of potentially non-substance addictive behaviors which become humongous threat among the adolescents such as digital addiction especially in online game addiction. This study argues that all type of addictions including online game addiction is related to common addiction components such as salience, mood modification and tolerance. Despite the plethora of digital addiction protection motivation, there is no standards or benchmarks used in secure intention behavior which involved the element of cybersecurity perspective in online game countermeasures. Hence, this study was organized to develop a conceptual model based on the former Protection Motivation Theory (PMT) in order to evaluate the secure intention behavior in online game addiction among adolescents. Driven by previous studies of online game addiction, we adopt all the distinct common components to measure underlying criteria which related to online game addiction to find the relationship between these constructs. As a result, this study will present the conceptual model as a secure intention behavior model in the context of online game addiction among adolescents. This conceptual model also has been validated by the expert in secure behavior together with related instruments. This conceptual model was expected to become as a reference model which can explain the relationship between human factors component and security factor like fear appeal which influence secure intention behavior in online game addiction. The researchers in this field also can use the model in different perspective and settings and thus create an avenue in paving the way towards online game addiction countermeasures especially in cybersecurity perspective.